Afterimages of Apartheid: Photography and Resistance - Thomas, Kylie (Routledge Contemporary South Africa, 2025)
Afterimages of Apartheid shows how photographs of the past can be mobilised as a critical tool for understanding the ongoing effects of apartheid in contemporary South Africa. Through close readings of significant images made during and after apartheid, the book shows how photography works as a means of documentation, commemoration, and resistance. Written by one of South Africa’s leading scholars of visual history, the book considers the ways in which photographs can be used to contest impunity for state violence. Afterimages includes chapters on the Sharpeville and Marikana massacres, on the re-opening of cases of human rights violations that remain unresolved in the aftermath of the South African Truth and Reconciliation Commission, and on contemporary protests against the post-apartheid state. The book makes a powerful case for the role of photographs in drawing the viewer into the past time they represent, issuing a call to the living to remember, respond, and react. This vivid account of the photography of apartheid will be of interest to students and researchers across the fields of South African history, visual studies, memory studies, art history, photography studies and transitional justice.